Towards cleaner heating production in rural areas: Identifying optimal regional renewable systems with a case in Ningxia, China. (December 2021) - He, Jiaming; Wu, Yunna; Wu, Junhao; Li, Shaoze; Liu, Fangtong; Zhou, Jianli; Liao, Mingjuan
Highlights: l A filter analysis on rural renewable energy technologies is carried out in detail. l A uniform evaluation system for hybrid renewable energy heating projects is introduced. l Subjective order relation analysis and objective entropy methods are combined. l A modified MULTIMOORA method is applied with a case study in China. l Renewable heating development recommendations are given based on the results. Abstract: Heating demand applied by fossil energy sources have inevitably caused tremendous carbon emissions. Renewable energy, in contrast, is more sustainable and desirable for heating but relevant decision-making process is yet in its infancy. This study thus promotes a decision framework for regional rural heating system driven by renewable energy sources (RES). A novel filter on six widely applied RES is introduced for smoother evaluation according to characteristic of the area in question, expertise and existing studies. The potentially feasible alternatives are then evaluated on a uniform criteria system identified from latest studies and empirical policy practices from economic, RE supply potential, environmental and social factors regardless of different types and combinations of RES for the first time. A novel integral weight method and an extended multi-objective optimization based on ratio analysis method are suggested by this paper and could contain arbitrary information during decision making process. The framework is then applied a real case study in Ningxia province, China. The result shows that based on local natural resources, a photovoltaic-wind-geothermal hybrid RES system performs the best. Further discussion justifies the framework and provide development and application recommendations for the RES technologies for regional and rural heating.